Human-induced hybridization and population bottleneck : population genetics, morphometrics and parasitology applied to the invaded and invasive tilapia Oreochromis mossambicus (Teleostei, Cichlidae) - (:unkn) unknown (My University, 2011)
Biological invasions are recognized as a significant evolutionary factor over short time scales. In particular, their effect is well recorded on the genetic structure of populations, the patterns of phenotypic evolution and the richness of parasite fauna associated to invasive populations. This study aims at quantifying the consequences of a biological invasion according to these three levels (genetical, phenotypical and parasitological) taking as example the Mozambique tilapia Oreochromis mossambicus. This African cichlid is characterized by an unusual conservation status since it is both (i) ranked among the world’s worst invasive species due to its global dispersion during the 20th century and (ii) sorted as “near-threatened” (IUCN) over its native range (a part of south-east Africa) because of massive hybridization with alien introduced Oreochromis species. The approach used in this study imply to describe the recent history of populations using nuclear (AFLP) and mitochondrial DNA (mtDNA) markers, and then to compare this genetic background to results describing the morphological and parasitological diversity of populations. Two different biological systems were studied: 1) Within the native range, the study focuses on the Lower Limpopo and the Changane sub-drainage (Mozambique). Introgression patterns involving the three co-occurring species were detected, but the frequency of hybrid is low and their geographic expansion is limited. These results provided rather good auspices for the conservation of O. mossambicus, and they allowed to identify two zones of high conservation priorities. The parasitological survey reveals high parasite richness and low prevalences among sites of low conservation values. This last pattern could favour the success of alien introduced species and their hybrids. 2) Among the invasive range of O. mossambicus, both AFLP and mtDNA support a strong genetic homogeneity and a low genetic diversity, a pattern interprete
Keywords: African Research